2018
DOI: 10.1163/15692086-12341343
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Impact of Arab Fathers

Abstract: Research over the past twenty years has found that fathers play an important role in their children’s development. However, the literature on fatherhood is still limited, particularly in the Arab world. This paper uses data from a mixed-method pilot study of sixty-one Arabs residing in the United Arab Emirates to examine the nature and impact of father involvement in the Arab region. The findings indicate that Arab fathers score highly on the good provider role, but low on responsible paternal engagement, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…8 Due to concerns of survey fatigue and in the interest of brevity, father involvement was focused on in this study given that existing literature has demonstrated its importance on self-esteem and education outcomes compared to mother involvement. See for example: Coltrane (1989), Fecht (2017, Lam et al (2012), Maslow (1987), Ridge & Jeon (2020), and Ridge et al (2018). 9 Dick's ( 2004) Fatherhood Scale is a 64-item instrument, composed of Likert-scale questions that ask respondents about their relationships with their fathers across nine subscales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Due to concerns of survey fatigue and in the interest of brevity, father involvement was focused on in this study given that existing literature has demonstrated its importance on self-esteem and education outcomes compared to mother involvement. See for example: Coltrane (1989), Fecht (2017, Lam et al (2012), Maslow (1987), Ridge & Jeon (2020), and Ridge et al (2018). 9 Dick's ( 2004) Fatherhood Scale is a 64-item instrument, composed of Likert-scale questions that ask respondents about their relationships with their fathers across nine subscales.…”
Section: Resultsmentioning
confidence: 99%
“…1 Borgonovi & Montt, 2012;Trautwein et al, 2006;OECD, 2010;Ridge & Jeon, 2020;Alsuwaidi, 20122 OECD, 2012Borgonovi & Montt, 2012;Hampen-Thompson et al, 2013, 246;Ho, 20103 Hill & Tyson, 2009Al-Taneiji, 2013;Borgonovi & Montt, 2012;Spera, 20054 Coltrane, 1989Lam et al, 2012;Maslow, 1987 5 Ridge & Jeon, 2020; Ridge et al, 2018;Fecht, 20176 MOHESR, 2015OECD, 2014OECD, , 2016Ridge, Kippels, & Chung, 2017 7 Although existing literature has argued that fathers in fact draw lines, we do not negate a mother-father relationship in which red-lines are developed and/or negotiated. That said, we encourage additional research that explores this critical space, and how policymakers can best support the optimal outcomes for families, communities, and the nation as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Arab culture, commitment to the family is key, and it is through family that religious and cultural notions of connection, obedience, and respect for elders are emphasized and ingrained (Oweis et al, 2012). Arab adolescents generally have a high degree of connectedness to their families; female adolescents, in particular, are known to be generally more connected to their families than males Ridge et al, 2018).…”
Section: Modern-day Arab Families and Women's Cdmmentioning
confidence: 99%
“…Arab women have become increasingly educated (Hamdan, 2006;Mazawi, 1999;Metcalfe, 2008;Ridge, 2014;World Bank, 2013), and have occupied more positions in the public sphere than ever before (Elamin & Omair, 2010). Yet, despite sociocultural reforms and modernization, the contemporary Arab world continues to retain some of its conservative traditions, values, and patriarchal social structures ( Jabeen, 2010;Metle, 2002;Sidani, 2005), including the emphasis on stereotypical gender roles in many families (Ridge et al, 2018).…”
Section: Modern-day Arab Families and Women's Cdmmentioning
confidence: 99%
See 1 more Smart Citation